Canal Irrigation Systems in India Operation, Maintenance, and Management - Chaube, Umesh Chandra; Pandey, Ashish; Singh, Vijay P. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
The book focuses broadly on the preliminaries of the canal irrigation systems in India with a focus on their operation, maintenance, and management of the canal systems. The chapters in this book are classified under four sections, viz., (i). preliminaries of the canal irrigation systems, (ii) operation of the canal irrigation systems, (iii) maintenance of the canal irrigation systems, and (iv) management of the canal irrigation systems. The preliminaries of the canal irrigation systems include an integrated view of irrigation and agriculture, irrigation management in India: problems, issues, a brief history, and some lessons, irrigation administration, organizational structure for management of irrigated agriculture, and farmers' participation. The operation of the canal irrigation systems includes the operation of dams and barrages, canal operation, water distribution planning, measurement of flow and sediment in canals, and performance evaluation of the canal irrigation system, use of groundwater in the canal command area. The canal irrigation systems' maintenance includes dams, barrages, related equipment, canals and related structures, field drainage, diagnostic analysis of canal irrigation system, soil and water quality management, soil moisture, and measurement. The management of the canal irrigation systems includes rehabilitation and modernization and a case study on rehabilitation, conjunctive use management, operation, and maintenance budgeting, and financing. The book is expected to be useful for academicians, water practitioners, scientists, water managers, environmentalists, administrators, NGOs, researchers, and students who are actively involved in the operation, maintenance, and management of the canal irrigation system for addressing the challenges being faced in the irrigated agricultural while addressing issues of canal irrigation systems in South East Asia.
An Integrated View of Irrigation and Agriculture -- Irrigation Management in India: Problems and Issues -- Irrigation in Indian Subcontinent: A Brief History and some lessons -- Irrigation Administration -- Organisational Structure for Management of Irrigated Agriculture -- Farmer's Participation -- Operation of Dams and Barrages -- Canal Operation -- Water Distribution planning. .
Keywords: Water; Hydrology; Environmental protection; Civil engineering; Agriculture; Environmental management; Sustainability; Water; Soil and Water Protection; Agriculture; Environmental Management; Sustainability